Hygienic assessment of frequency of consuming food products of animal origin in the diet of medical students and rationale of ways of its correction. - L. B. Yeltsova; S. T. Omelchuk; A. A. Petrosian (Medičnì Perspektivi)
Availability of various healthy food products in the student’s diet and conscious student’s choice represents the best way of prevention of the alimentary and alimentary-associated diseases, preservation and promotion of health. The aim of the study: hygienic assessment of frequency of consuming food products of animal origin by medical students in order to prevent alimentary diseases by means of correction of diet. The authors studied medical students’ diet using map questionnaire with the subsequent data assessment. The study includes the data of 858 respondents, students of the 2nd, 4th and 6th years of study of medical faculties of O.O. Bogomolets National Medical University. Random sampling was used. The age of the respondents ranges between 18 and 25 years, 570 females and 288 males. Frequency of consumption was estimated according to the following categories: consuming of food products of animal origin once a day or even more often, consuming them almost every day, consuming them once a week, consuming them several times a week, consuming them once or several times a month, consuming them rarely or never. The study assessed frequency of consumption of such product groups as: meat and meat products, fish and seafood, milk and dairy products, eggs and fatty products. The authors have established that one third of the respondents, regardless of their gender and year of study, consume meat and meat products once a day or almost every day. From 20% (the 2nd year of study) to 28% (the 6th year of study) of male respondents and from 13% (the 2nd year of study) to 21% (the 6th year of study) of female respondents consume fish and seafood once a week or several times a week. Less than 30% of both male and female respondents, without regard to the year of study, consume milk and dairy products once a day or even more often.  About 20% of male respondents and from 10% (the 2nd year of study) to 25% (the 6th year of study) of female respondents consume eggs daily. 16-18% of male respondents and 6-10% of female respondents consume fatty products (butter, lard) daily or almost every day. The obtained results make it possible to conclude that more than 2/3 of the medical students’ diets according to the frequency of consuming food products of animal origin do not correspond to the National recommendations on nutrition precisely by the frequency of their consumption [12, 13]. This may lead to polynutrient deficiency and development of alimentary diseases, which proves the necessity of correction of medical students’ diet.